2021
DOI: 10.4038/cjs.v50i3.7904
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm biofertilizer can reinstate network interactions for improved rice production

Abstract: Biofilms are complex communities of multiple microbial species which are attached to surfaces or physical interfaces in nature. Such biofilms can also be developed in vitro using beneficial microbes, and can be used as Biofilm biofertilizers (BFBFs). Once applied, the BFBFs can supply sub network components to the bulk network of soil-plant-microbe parameters in agro-ecosystems degraded due to excessive use of chemical inputs. Thus, the degraded ecosystems can get their bulk network repaired through the sub ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Thalwita, Minuwangete, and Galgamuwa to compare two fertilizer practices MOP 60 kg ha − 1 ), recommended by the Department of Agriculture, Sri Lanka (2013)]. These practices are currently used by farmers in Sri Lanka [30][31][32]. The research sites had a typical subtropical climate with a mean annual rainfall of ca.…”
Section: Methodology Experimental Designmentioning
confidence: 99%
“…Thalwita, Minuwangete, and Galgamuwa to compare two fertilizer practices MOP 60 kg ha − 1 ), recommended by the Department of Agriculture, Sri Lanka (2013)]. These practices are currently used by farmers in Sri Lanka [30][31][32]. The research sites had a typical subtropical climate with a mean annual rainfall of ca.…”
Section: Methodology Experimental Designmentioning
confidence: 99%
“…These interactions are signal-mediated between plants and microbes. The balance of these interactions will determine the stability and continuity of agroecosystem functions [36]. By administering BFBF to plants, the network will be improved, which will have a positive impact on plant growth, yields, and soil quality.Several studies revealed the positive impact of using BFBF on various plants (Table 1).…”
Section: Benefit Of Biofilm Biofertilizermentioning
confidence: 99%
“…Applying BFBF to rice plants in multiple regions of Sri Lanka can reduce the use of inorganic fertilizers by approximately 50% and increase grain yield by approximately 25%. [36]. BFBF has the potential as an environmentally friendly and economical method because it can reduce the use of inorganic fertilizers.…”
Section: Benefit Of Biofilm Biofertilizermentioning
confidence: 99%
“…1 and 2). In the soil, microbial bio lms developed in vitro are reported to reinstate lost microbial diversity in degraded agroecosystems as explained above [11], thus leading to restore network interactions for improved rice production in large scale cultivations [9,23]. The same mechanism could have operated here to increase the live microbial cell concentrations of the gut microbes, because the gut microbial diversity is a subset of soil microbial diversity [6].…”
Section: Breaking Dormancy Of Gut Microbes Using Bfexmentioning
confidence: 99%